TECHNOGENIC EFFECTS ON THE LITHOSPHERE AND ITS ECOLOGICAL CONSEQUENCES - Yarboboev , Tulkin Nurboboboevich; Kosimova , Karima Yodgor kiz (Educational Research in Universal Sciences, 2023)
The results of anthropogenic impacts on the most important components of the lithosphere, accompanying numerous production processes, including the extraction of raw materials, production of construction materials, etc., are considered. The main directions of assessment of technogenic impacts on the lithosphere and their environmental consequences are given.